Acute effects of Gua Sha on thoracolumbar fascia thickness and related physiological parameters in healthy young people: A randomized controlled trial - Wang, Beibei; Hu , Yang; Chen, Hongxiu; Lai, Dehui; Eungpinichpong, Wichai (Asia-Pacific Journal of Science and Technology, 2025)
This study explores the potential mechanism of single Gua Sha therapy on thoracolumbar fascia thickness and related physiological parameters in 66 healthy individuals randomly assigned to a 15-min Gua Sha group or a 15-min rest control group. Thoracolumbar fascia thickness, pressure pain threshold, tissue hardness, skin temperature, lumbar spine flexibility, stress index, and heart rate variability were assessed before and immediately after the interventions. The results revealed a significant reduction in thoracolumbar fascia thickness in the Gua Sha group (Left side: a reduction of 0.06 mm, p<0.05, effect size 0.14; Right side: a reduction of 0.09 mm, p<0.05, effect size 0.22). Skin temperature also increased significantly (mean difference: 0.64 °C, 95% CI: 0.57–0.71, p<0.001), and thoracolumbar fascia improved (mean difference: 0.75, 95% CI: 0.27–1.22, p<0.01), suggesting a softening effect of Gua Sha on the fascia. However, contrary to the hypothesis, the Gua Sha group showed a decreased pressure pain threshold and increased tissue hardness. Both interventions effectively reduced the stress index and enhanced heart rate variability, although there were no significant differences between the groups (p＞0.05). In conclusion, this study found that a single session of Gua Sha therapy could induce a subtle but significant reduction in thoracolumbar fascia thickness and improve specific physiological parameters in healthy individuals, but the unexpected findings regarding the pressure pain threshold and tissue hardness require further investigation to elucidate the underlying mechanisms, offering insight into Gua Sha’s possible mechanisms.